Impact of environmental arsenic exposure on human health - a narrative review - Szada-Borzyszkowski, Kacper; Owczarenko, Konstancja; Filipski, Michał; Wróbel, Bartosz; Wójcik, Lena; Gadzalski, Krzysztof (Journal of Education, Health and Sport, 2026)
Background. Arsenic is a naturally occurring metalloid known for its toxicity. Due to industrial activity and environmental pollution, human exposure, mainly through contaminated water and food, has become a global health problem. Aim. This review aims to present the main sources of arsenic exposure, its mechanisms of toxicity, and the clinical features and management of poisoning. Material and methods. A narrative review of the literature was conducted, focusing on environmental exposure, pathophysiology, and clinical aspects of arsenic toxicity. Results. Arsenic enters the body mainly through ingestion and inhalation, with groundwater and rice being key sources. The inorganic forms, especially trivalent arsenic, are the most toxic. After absorption, arsenic affects multiple cellular processes, leading to oxidative stress, enzyme inhibition, and impaired energy production. Acute poisoning typically presents with gastrointestinal symptoms, while chronic exposure leads to multisystem damage involving the skin, nervous, cardiovascular, and endocrine systems, and increases cancer risk. Diagnosis is based on history and arsenic levels in urine or hair. Treatment includes chelation therapy and supportive care. Conclusions. Arsenic exposure remains an important but often overlooked health risk. Early recognition and limiting exposure are crucial, and prevention should remain a priority in affected regions.